A formulação das políticas públicas para a juventude rural no Brasil e os elementos constitutivos desse processo social - Barcellos, Sérgio Botton (2015)
The construction of the research problem occurred in trying to investigate the configuration of public policies for the rural youth and how this political agenda was introduced in the State of the Brazil. The main issue in the research is how the process of configuration of public policies for rural youth in federal government has occurred. The methodology for this study used was qualitative research procedures were triggered participant observation, interviews and documentary analysis. During the research the actors, the formulated policies and rural youth category expressed during this process were highlighted